2014
DOI: 10.1186/preaccept-2103142870137452
|View full text |Cite
|
Sign up to set email alerts
|

The speed of kill of fluralaner (Bravecto¿) against Ixodes ricinus ticks on dogs

Abstract: Background: Pathogens that are transmitted by ticks to dogs, such as Anaplasma phagocytophilum, Babesia spp., Borrelia burgdorferi sensu latu, and Ehrlichia canis, are an increasing problem in the world. One method to prevent pathogen transmission to dogs is to kill the ticks before transmission occurs. Fluralaner (Bravecto™) is a novel isoxazoline insecticide and acaricide that provides long persistent antiparasitic activity following systemic administration. This study investigated the speed of kill of flura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Until 2014, tick control compounds for dogs were available as spot-ons, sprays or collars exhibiting its tick-killing efficacy via blood meal and/or contact exposure/repellency [13]. In the speed of kill studies from Wengenmayer et al [9], it was demonstrated that orally-administered fluralaner starts to kill ticks present on the dog as early as 4 h (89.6 %), showing almost complete tick-killing efficacy within 12 h after treatment over the entire 12-week period of efficacy. These results are confirmed in this study by the excellent efficacy results against ticks (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 2014, tick control compounds for dogs were available as spot-ons, sprays or collars exhibiting its tick-killing efficacy via blood meal and/or contact exposure/repellency [13]. In the speed of kill studies from Wengenmayer et al [9], it was demonstrated that orally-administered fluralaner starts to kill ticks present on the dog as early as 4 h (89.6 %), showing almost complete tick-killing efficacy within 12 h after treatment over the entire 12-week period of efficacy. These results are confirmed in this study by the excellent efficacy results against ticks (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…As fluralaner is a systemic acting ectoparasiticide; its efficacy depends on ticks attaching to the host’s skin and commencing to feed, thereby ingesting the active compound. Due to its rapid speed of killing within 12 h after tick attachment [9], the potential of orally administered fluralaner to prevent B. canis transmission was tested in the outlined study.…”
Section: Introductionmentioning
confidence: 99%
“…This requirement is generally understood by the animal health industry, and most products marketed recently have been tested and compared for the speed of their onset of action Wengenmayer et al, 2014;Beugnet et al, 2016;Blair et al, 2016;. Recent compounds deriving from the fairly new chemical class of isoxazolines (Weber and Selzer, 2016) exhibit their ectoparasitic action against both, insects and acari of veterinary importance, within hours, and certainly reduce the risk of Survival in flea feces estimated to be at least 3 days.…”
Section: Drug Profile For Blocking Pathogen Transmissionmentioning
confidence: 99%
“…Therefore, requirements for new ectoparasitic drugs should include not only the control of ectoparasites for a certain period of time, but also address their ability to block the transmission of the various vector-borne pathogens by a rapid onset of action. In this scope, "speed of kill" has become an important commercial differentiator for recent marketed products Wengenmayer et al, 2014;Beugnet et al, 2016;Blair et al, 2016; and many studies have been designed for testing the ability of those products to block transmission of some important pathogens of cats like Bartonella henselae (Bradbury and Lappin, 2010), and of dogs like Dipilidium caninum (Fourie et al, 2013a), Leishmania infantum (Brianti et al, 2014), Ehrlichia canis (Jongejan et al, 2015), Borrelia burgdorferi, Anaplasma phagocytophilum (Honsberger et al, 2016), and Babesia canis Taenzler et al, 2016). These studies all report a complete prevention of pathogen transmission by fast elimination of the vector.…”
Section: Introductionmentioning
confidence: 99%
“…Fluralaner, afoxolaner and sarolaner are recently introduced isoxazoline acaricides, and are administered orally and distributed systemically. Systemically distributed acaricides can kill attached ticks at any location on the body when the tick feeds [8, 10]; therefore, systemically distributed isoxazolines may be expected to have better immediate efficacy, because they are quickly and widely distributed in the blood circulation. Cutaneously distributed acaricides depend on diffusion to spread over the body surface on the skin, typically in the lipid layer [8].…”
Section: Introductionmentioning
confidence: 99%